Walnut supplementation after fructose-rich diet is associated with a beneficial fatty acid ratio and increased ACE2 expression in the rat heart - Bošković, Maja; Živković, Maja; Koricanac, Goran; Tepavcevic, Snezana; Zec, Manja; Debeljak-Martacic, Jasmina; Stanković, Aleksandra (Frontiers in Physiology, 2022)
Increased fructose consumption has been linked with chronic inflammation and metabolic syndrome (MetS). Activation of renin-angiotensin system (RAS) and NF-κB have been detected in MetS. Walnuts are a rich source of polyunsaturated omega-3 fatty acids (n-3 PUFA) that were suggested to exert anti-inflammatory effects related to cardio-metabolic health. We hypothesized that walnut supplementation has the capacity to revert unfavorable fructose rich diet (FRD)-induced activation of cardiac RAS and NF-κB in male rats. Due to the lack of similar studies, we investigated the effects of walnut supplementation (6 weeks) on the expression of four RAS molecules (ACE, ACE2, AT1R and AT2R) and NF-κB in rat heart after FRD (10% w/v, 9 weeks). In addition, we followed the changes in n-6/n-3 PUFA ratio in total pool of heart lipids after both treatments to elucidate the walnut effects on fatty acids in the heart. 36 animals (9 per group) participated in the experiment. FRD significantly increased ACE protein level in the heart (p < 0.001). Walnut supplementation significantly increased ACE2 protein level in the heart of FRD (p < 0.001). In addition, walnut supplementation showed a significant main effect on the arachidonic acid/eicosapentaenoic acid ratio (p = 0.004). Walnut supplementation significantly reduced this ratio, in comparison with both, the control group (C vs. FW, p < 0.05) and the FRD group (F vs. FW, p < 0.05). However, walnut treatment failed to revert significant effect of fructose (p < 0.001) on elevation of NF-κB protein level. Our results suggest beneficial effect of walnut supplementation on ACE2 protein level and n-6/n-3 PUFA levels in the heart of animal model of MetS. Such results highlight the approach of omega-3 rich walnut supplementation in stimulation of endogenous production of favorable molecules in the heart which could be affordable nutritional treatment in maintenance of cardio-metabolic health.